Republic of Croatia Justice Sector Public Expenditure and Institutional Review : Resourcing the Justice Sector for Efficiency and Performance - World Bank (Washington, DC, 2014)
Croatia, the newest member-state of the European Union (EU), undertook significant justice reforms during the last decade. Many were part of its justice-related EU accession process, including the enactment and implementation of new laws and amendment of others, improved case management and enforcement and computerization of land registers. Benchmarking Croatia's justice sector indicates that it compares well with other European countries on several aspects of performance including resource indicators important for a functioning justice sector. However, the positive achievements and the deployment of significant resources have been offset by less-than-expected levels of overall performance, with high and growing demand for justice services facing an inadequate supply response. This report tries to lift the veil on the reasons behind justice sector underperformance despite relatively adequate budgetary allocations, comparatively high staffing levels, and a dense network of courts and prosecution offices. It provides a snapshot of Croatia's justice sector and of different aspects of its performance. It reviews the evolution of and trends in justice sector expenditures. It gives an assessment of sector expenditure management policies and practices. The report examines demand and supply issues in depth, juxtaposing data on caseloads, case disposals, and expenditures to identify implications for efficiency improvements. The report uses a supply-demand approach to assess the real challenges to improving sector performance, focusing on resource management, and allocation issues on the supply side and on case inflow on the demand side.